Bone Regeneration: A Magnesium‐Enriched 3D Culture System that Mimics the Bone Development Microenvironment for Vascularized Bone Regeneration (Adv. Sci. 12/2019). Issue 12 (19th June 2019) - Lin, Sihan; Yang, Guangzheng; Jiang, Fei; Zhou, Mingliang; Yin, Shi; Tang, Yanmei; Tang, Tingting; Zhang, Zhiyuan; Zhang, Wenjie; Jiang, Xinquan
Abstract : Inspired by the correlation between MagT1 and embryonic bone development, a magnesium‐enriched 3D culture system is fabricated to provide embryonic‐like microenvironment for stem cells in article number1900209 by Wenjie Zhang, Xinquan Jiang, and co‐workers. Mg 2+ via MagT1 stimulates both osteogenic differentiation and neovascularization. An obvious vascularized bone regeneration is achieved in vivo using such magnesium‐enriched cell vehicles.